Pelatihan Penulisan Artikel Ilmiah Untuk Guru-Guru Di Kota Waringin Timur - Misnawati Misnawati; Petrus Poerwadi; Alifiah Nurachmana; Patrisia Cuesdeyeni; Linggua Sanjaya Usop; Lazarus Linarto; Paul Diman; Yuliati Eka Asi; Albertus Purwaka; Nirena Ade Christy; Stefani Ratu Lestariningtyas; Indra Perdana; Ibnu Yustiya Ramadhan; Syarah Veniaty (Community : Jurnal Pengabdian Pada Masyarakat, 2023)
This training aims to enhance the ability of teachers in East Waringin Timur City to write scholarly articles, enabling them to contribute more effectively to the educational development in the region. In an effort to achieve this goal, the outreach team will undertake various activities, including interviews with teachers, curriculum analysis, surveys, literature research, and communication with schools. This study will provide a deeper insight into the needs and expectations of teachers regarding scholarly article writing, as well as facilitate the development of a Scholarly Article Writing training program tailored to the local educational context. It is expected that the results of this outreach will bring about positive benefits in improving the quality of education in East Waringin Timur City.